THE DEVELOPMENT OF FUNDAMENTAL MOVEMENT-BASED LEARNING USING WATER GAMES FOR CHILDREN 5 – 6 YEARS - Rizki Kurniati (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2017)
The purpose of this research are; (1) develop fundamental movement based learning using water games for children 5-6 years and (2) obtain empirical data on the effectiveness of the results of model development fundamental movement based learning using water games for children aged 5-6 years. Subjects in this study were children aged 5-6 years in kindergarten. Place of research conducted in the city of Palembang. This study is the development of the Research and Development of Borg and Gall. Product results of the research is a fundamental movement guidebook using water games. Research shows that: (1) the development of fundamental movement based learning using water games for children aged 5-6 years have been declared invalid by a motor learning, physical activity experts and practitioners of early childhood education, (2) fundamental movement based learning using water games proved 85% can improve fundamental skills and helps to build a sense of confidence and courage.Keywords: fundamental movement, water games, children aged 5-6 years.